Modes of pulsating auroras and related geomagnetic pulsations - Oguti, Takasi (1982)
P(論文) Display modes of pulsating auroras were examined in reference to classifications previously proposed. It is concluded that the pulsating auroras are reasonably classified into, 1) pure pulsations, 2) poleward propagation, 3) streaming along structures, 4) flooding beyond patch boundaries, 5) equatorward propagation, and 6) flash, all in horizontal structures or movements. Most of the modes are related to concurrent geomagnetic pulsations with a peak-to-peak correspondence, within a few seconds. The magnetic pulsations observed under the pulsating aurora are thus concluded to be consequences of the fluctuation in the ionospheric electric current caused by fluctuations in electric conductivity due to pulsating auroral precipitations. departmental bulletin paper